Humour in Rabindranath Tagore's selected early short stories: a freudian reading - Quayum, Mohammad Abdul (Flinders University, Australia, 2014)
This essay is intended to fill the gap in the discussion of humour in Rabindranath Tagore’s writings, particularly his short stories. It argues that although Tagore is often seen as a serious writer, dealing with significant issues concerning religion, politics and culture in his work, he also had a lighter side to his personality, which enabled him to laugh at certain inherent human weaknesses, such as excessive piety, sentimentality, affectedness, arrogance and sexual jealousy, in a comic spirit, rather than being derogatory or sarcastic about them. Sometimes, this laughter was even at his own expense, caricaturing a certain drollery or oddity in his own personality, or at the expense of a close family or associate. The essay investigates four of Tagore’s short stories – “The Path to Salvation” (Muktir Upai), “The Professor” (Addhyapak), “Privacy” (Sadar O Andar) and “The Auspicious Sight” (Subhadristi) – all written during the first phase of his writing career, when he was living at Shelaidah, East Bengal, to bring home the argument that during these early years Tagore was capable of responding to life in its fullness. Thus he could empathise with its sorrows and sufferings as much as relishing its mirth and amusement, which he saw as an inalienable part of the human experience. Furthermore, the humour we encounter in these four stories is different from that in his later stories – such as “Kabuliwala,” “The Editor” (Symapadak), “Number One” (Paila Number) and “Deliverance” (Uddhar) – in that they are written in a tender and sympathetic tone, merely to tease and prod, vis-ŕ-vis his use of, in Freud’s phrases, “tendency wit” or “tendency comedy” in the latter stories.